Reproducibility in Psychological Science: When Do Psychological Phenomena Exist? - Iso-Ahola, Seppo E. (Frontiers in Psychology, 2017)
ABSTRACT Scientific evidence has recently been used to assert that certain psychological phenomena do not exist. Such claims, however, cannot be made because (1) scientific method itself is seriously limited (i.e., it can never prove a negative); (2) non-existence of phenomena would require a complete absence of both logical (theoretical) and empirical support; even if empirical support is weak, logical and theoretical support can be strong; (3) statistical data (e.g., effect size) are only one piece of evidence; psychological phenomena cannot be reduced to statistical phenomena; and (4) psychological phenomena vary across time, situations and persons. Therefore, a declaration that a phenomenon (e.g., the self-control depletion effect) is not real is not only theoretically and empirically unjustified but runs counter to the propositional and provisional nature of scientific knowledge. There are only “temporary winners” and no “final truths” in scientific knowledge. Psychology is a science of subtleties in human affect, cognition and behavior. Its phenomena fluctuate with conditions and may sometimes be difficult to detect and reproduce empirically. When strictly applied, reproducibility is an overstated and even questionable concept in psychological science. Furthermore, the magnitude of an effect (effect size) is a poor indicator of relevance and importance of phenomena (cf. “deliberate practice” vs. “talent” in expert performance), not to mention whether they are real or unreal. To better understand psychological phenomena, their theoretical and empirical properties should be examined through multiple parameters and criteria. Ten such parameters are suggested. Keywords: reproducibility, replication, meta-analysis, psychological phenomena